Method for preparing lithium iron manganese phosphate by obtaining high-performance precursor from waste lithium iron phosphate

By using phytic acid to form a complex during the wet recycling process to restrict the fusion of iron phosphate particles, the performance degradation caused by high-temperature dehydration was solved, and a high-performance lithium manganese iron phosphate cathode material was prepared.

CN121376936APending Publication Date: 2026-01-23NANJING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511331424.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-17
Publication Date
2026-01-23

AI Technical Summary

Technical Problem

During wet recycling, iron phosphate particles tend to fuse and enlarge during high-temperature dehydration, affecting the performance of lithium manganese iron phosphate.

Method used

Phytic acid was added to the leachate of waste lithium iron phosphate as a chelating agent to form a stable complex, which restricted the fusion of iron phosphate particles. Dehydrated iron phosphate was obtained by high-temperature calcination and used as a precursor for lithium manganese iron phosphate.

Benefits of technology

The prepared lithium manganese iron phosphate cathode material exhibits better performance, including better reversibility, impedance and rate performance, as well as higher discharge specific capacity and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121376936A_ABST
    Figure CN121376936A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing lithium iron manganese phosphate by obtaining a high-performance precursor from waste lithium iron phosphate. According to the method disclosed by the invention, the chelating effect of phytic acid and ferric ions is utilized, so that an organic carbon source is introduced into hydrated iron phosphate precipitated from the waste lithium iron phosphate leaching solution, the fusion growth of iron phosphate particles is effectively prevented in the subsequent high-temperature roasting process, and the high-performance lithium manganese iron phosphate precursor is obtained from the waste lithium iron phosphate. The method comprises the following steps: dissolving waste lithium iron phosphate powder in a sulfuric acid solution, then adding a small amount of a phytic acid solution and ferric sulfate with a corresponding molar weight, precipitating and calcining at a high temperature to obtain dehydrated iron phosphate (FP-PA) with a limited particle size; when the material is applied to synthesis of a lithium manganese iron phosphate positive electrode material, the particle size of the positive electrode material can be effectively controlled, and the specific capacity and cycle performance of a battery are improved. The method is easy to operate and high in repeatability, and a new way is provided for treating waste lithium iron phosphate with economic benefits and excellent performance.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of recycling of waste lithium ion battery positive electrode materials, and particularly relates to a method for obtaining a high-performance precursor for preparing lithium manganese iron phosphate from waste lithium iron phosphate, and application in lithium ion battery recycling and reuse. BACKGROUND

[0002] With the development of portable electronic devices and electric vehicles, and the demand for renewable energy (wind and solar) grid-connected energy storage, the use of lithium ion batteries has shown explosive growth. Among the many positive electrode materials such as lithium cobaltate (LiCoO2), lithium manganate (LiMn2O4), lithium iron phosphate (LiFePO4), and ternary materials (NCM / NCA), lithium iron phosphate is widely used due to its good safety performance, low price, and strong cycle life. With the decline in subsidies and the promotion of energy storage systems, its proportion is further increasing.

[0003] The service life of lithium iron phosphate batteries is generally 5-8 years, so a large number of waste lithium iron phosphate batteries will be generated over time. Retired batteries contain a large amount of toxic components and valuable metals, which can effectively prevent toxic substances from polluting soil and water sources and protect the environment and public health through recycling; at the same time, lithium, cobalt, nickel, and other scarce metals can be extracted to alleviate resource shortages and reduce mining energy consumption.

[0004] Currently, there are three methods for recycling waste lithium iron phosphate batteries: pyrometallurgical recycling, hydrometallurgical recycling, and direct recycling. Pyrometallurgical recycling uses high-temperature incineration or smelting technology to remove organic matter in the battery and recover valuable metals. Although the process is simple, it has the disadvantages of high energy consumption, harmful gas emissions, and low product purity. Direct recycling restores or approaches the initial performance of waste materials by repairing crystal structure defects and supplementing lithium ions. Although it has the advantages of high resource utilization, low energy consumption, and environmental friendliness, the source of waste batteries is complex, and the performance and state of batteries from different batches and different manufacturers differ greatly, which greatly hinders its large-scale application. Hydrometallurgical recycling uses acids, bases, and salts to dissolve the metals in the battery into a solution, and then separates and extracts the metals one by one through precipitation and extraction. Due to its high resource recovery rate and wide applicability, hydrometallurgical recycling is widely used.

[0005] In the wet recovery, after the waste lithium iron phosphate material is dissolved, the pH is adjusted by an alkaline solution, and an important precursor of hydrated iron phosphate for subsequent synthesis of lithium iron phosphate and lithium manganese iron phosphate can be obtained. Before synthesizing the positive electrode material, the hydrated iron phosphate is usually subjected to high-temperature dehydration treatment to avoid the influence of the combined water on the purity and performance of the positive electrode material in the synthesis process. However, during the high-temperature treatment, the hydrated iron phosphate is inevitably dehydrated, and the particle fusion increases at the same time, which has an influence on the performance of the subsequent lithium iron phosphate and lithium manganese iron phosphate that cannot be ignored. SUMMARY

[0006] To solve the problems in the above background, the present application provides a method for preparing lithium manganese iron phosphate from waste lithium iron phosphate, which solves the problems of large iron phosphate particles in the traditional wet recovery and poor performance of lithium manganese iron phosphate synthesized by using the iron phosphate particles as a precursor.

[0007] The technical scheme provided by the present application is as follows:

[0008] A method for preparing lithium manganese iron phosphate from waste lithium iron phosphate, wherein a small amount of phytic acid is added to the leaching solution of the waste lithium iron phosphate. Phytic acid is a strong chelating agent that can form stable complexes with various metal ions, including ferric ions in the leaching solution. When the pH of the leaching solution is adjusted and iron phosphate is precipitated, the six phosphate groups in the phytic acid molecules can form stable complexes with the ferric ions. During the high-temperature calcination of the precipitated hydrated iron phosphate, the phosphate groups chelated with the ferric ions are carbonized with the connected inositol ring, which limits the fusion of the iron phosphate particles. The dehydrated iron phosphate (FP-PA) modified by the carbon derived from phytic acid is used as a precursor of lithium manganese iron phosphate, and the synthesized positive electrode material has excellent performance. The specific preparation steps are as follows:

[0009] (1) Discharge and disassemble the waste lithium iron phosphate battery in the salt water to obtain lithium iron phosphate positive electrode sheets, graphite negative electrode sheets, and separators.

[0010] (2) Treat the obtained lithium iron phosphate positive electrode sheets in a muffle furnace at 500 DEG C to obtain waste lithium iron phosphate positive electrode powder and aluminum foil.

[0011] (3) Weigh a certain amount of waste lithium iron phosphate positive electrode powder and disperse it in a certain amount of sulfuric acid solution, and place it in an 80 DEG C oil bath to dissolve it.

[0012] (4) Add a certain amount of phytic acid solution and ferric sulfate so that the molar number of phosphorus and iron elements is the same.

[0013] (5) Add a certain amount of alkaline solution to adjust the pH of the above solution to about 2 to obtain hydrated iron phosphate; add sodium carbonate, and wash the precipitate with deionized water to obtain lithium carbonate.

[0014] (6) In a tube furnace, inert gas is introduced, and dehydrated iron phosphate (FP-PA) is obtained by calcination at high temperature for a certain period of time.

[0015] Further, in step (3), the ratio of the powder to the solution is 2-5 g / 100 ml; preferably, the ratio of the powder to the solution in step (3) is 5 g / 100 ml.

[0016] Further, in step (4), the phosphorus content of the added phytic acid is 3%-10% of the phosphorus content of the waste lithium iron phosphate; preferably, the phosphorus content of the phytic acid in step (4) is 5% of the phosphorus content of the waste lithium iron phosphate.

[0017] Further, in step (5), the alkaline solution is one of an ammonia solution, a sodium hydroxide solution, and a potassium hydroxide solution; preferably, the alkaline solution in step (5) is an ammonia solution. BRIEF DESCRIPTION OF DRAWINGS

[0018] Figure 1 SEM image of the hydrated iron phosphate synthesized in Example 1 of the present application.

[0019] Figure 2 SEM image of the dehydrated iron phosphate (FP-PA) synthesized in Example 1 of the present application.

[0020] Figure 3 SEM image of LiMn 0.5 Fe 0.5 PO4-PA synthesized in Example 2 of the present application.

[0021] Figure 4 XRD image of LiMn 0.5 Fe 0.5 PO4-PA synthesized in Example 2 of the present application.

[0022] Figure 5 (a) and (b) are, respectively, cyclic voltammograms of LiMn 0.5 Fe 0.5 PO4-PA batteries and LiMn 0.5 Fe 0.5 PO4 batteries assembled in Example 4 of the present application at different scan rates.

[0023] Figure 6 (a) and (b) are, respectively, in-situ impedance plots of LiMn 0.5 Fe 0.5 PO4-PA batteries and LiMn 0.5 Fe 0.5 PO4 batteries assembled in Example 4 of the present application.

[0024] Figure 7This is a rate performance diagram of the button cell assembled in Embodiment 4 of the present invention.

[0025] Figure 8 This is a cycle performance diagram of the coin cell assembled in Embodiment 4 of the present invention at a 1C rate. Detailed Implementation

[0026] The present invention will be described more fully below with reference to specific embodiments and accompanying drawings, but the present invention is not limited thereto.

[0027] Unless otherwise specified, the experimental methods described in the following examples are conventional methods.

[0028] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.

[0029] Example 1

[0030] Obtaining high-quality dehydrated iron phosphate (FP-PA) from waste lithium iron phosphate.

[0031] Waste lithium iron phosphate (LFP) batteries were discharged in salt water and then disassembled to obtain LFP positive electrode sheets, graphite negative electrode sheets, and a separator. The obtained LFP positive electrode sheets were treated in a muffle furnace at 500℃ for 5 hours to obtain waste LFP positive electrode powder and aluminum foil. 3g of waste LFP positive electrode powder was weighed using a balance and dispersed in 18ml of sulfuric acid solution and 100ml of deionized water, and then dissolved in an 80℃ oil bath. A certain amount of phytic acid solution and ferric sulfate were added to maintain a phosphorus-to-iron ratio of approximately 1:1. A certain amount of alkaline solution was added dropwise to adjust the pH of the solution to approximately 2, yielding hydrated ferric phosphate. Sodium carbonate was added, and the precipitate was washed with deionized water to obtain lithium carbonate. The hydrated ferric phosphate was placed in a tube furnace, purged with argon gas, and calcined at 350℃ for 4 hours to obtain dehydrated ferric phosphate (FP-PA).

[0032] SEM testing was performed on hydrated ferric phosphate, such as... Figure 1 As shown; SEM testing was performed on dehydrated ferric phosphate (FP-PA), as follows. Figure 2 As shown in the figure, SEM images show that after high-temperature calcination, the iron phosphate particles did not undergo fusion growth.

[0033] Example 2

[0034] FP-PA Synthesis of LiMn 0.5 Fe 0.5 PO4-PA materials

[0035] Manganese carbonate, ammonium dihydrogen phosphate and lithium carbonate and dehydrated iron phosphate obtained in Example 1 were weighed according to the molar ratio of Li:Fe:Mn:P = 1:0.5:0.5:1, 2 g in total, and 0.3 g of glucose was weighed. 5 ml of anhydrous ethanol was measured, and the weighed powder and the measured liquid were mixed together, and after oscillation, it was poured into a zirconium oxide ball mill jar. 20 g of zirconium oxide milling beads was added, and the ball milling was carried out at a speed of 200 rpm for six hours. The milled solution was poured into a glass beaker and placed in an 80°C oven for 12 hours. The baked block was ground to powder in a mortar. The above-mentioned powder was placed in a quartz tube, and the quartz tube was pumped to negative pressure using a vacuum pump and argon was introduced to raise the gas pressure to the outside pressure of the tube, which was repeated three times. The tube furnace was raised to 350°C for 3 h and then to 700°C, and the temperature was kept for 10 hours in an argon atmosphere; during the solid-phase sintering process, the precursor gradually nucleated and grew, and the synthesized lithium manganese iron phosphate positive electrode powder was obtained by cooling to room temperature, denoted as LiMn 0.5 Fe 0.5 PO4-PA.

[0036] The LiMn 0.5 Fe 0.5 PO4-PA was subjected to SEM test, as shown in Figure 3 , the particle size of the lithium manganese iron phosphate material was mainly distributed in 50-200 nm. The LiMn 0.5 Fe 0.5 PO4-PA was subjected to XRD test, as shown in Figure 4 , the characteristic peaks of the synthesized lithium manganese iron phosphate were obvious, and the diffraction peak intensity was high.

[0037] Example 3

[0038] LiMn 0.5 Fe 0.5 PO4-PA material preparation to form electrode wafer

[0039] The obtained LiMn 0.5 Fe 0.5 PO4-PA material, SuperP and polyvinylidene fluoride (PVDF) were mixed and dispersed in N-methyl pyrrolidone (NMP) solution at a mass ratio of 8:1:1, and magnetic stirring was carried out for 10 hours to obtain a uniformly dispersed positive electrode slurry. The mixed slurry was coated on an aluminum foil, and after drying in a vacuum oven at 80°C for 12 hours, it was cut into 12 mm wafer. The mass loading of the positive electrode was about 2-2.5 mg / cm 2 .

[0040] Example 4

[0041] LiMn 0.5 Fe 0.5 PO4-PA material applied to lithium ion battery

[0042] With the wafer obtained in Example 3 as the positive electrode, lithium foil as the negative electrode, polypropylene as the separator, 15 μL electrolyte added on both sides of the positive and negative electrodes, and in the order of positive electrode shell, positive electrode, electrolyte, separator, electrolyte, negative electrode, gasket, spring, negative electrode shell, it was assembled into a CR2032 button cell in a glove box with water and oxygen concentrations below 0.1 ppm. The assembled battery was allowed to stand at 27°C for 6 h before electrochemical performance testing.

[0043] As a comparison, LiMn 0.5 Fe 0.5 PO4was synthesized and assembled into batteries. LiMn 0.5 Fe 0.5 PO4-PA was different from LiMn 0.5 Fe 0.5 PO4, the precursor of LiMn

[0044] Figure 5 (a) (b) are the cyclic voltammograms of LiMn 0.5 Fe 0.5 PO4-PA and LiMn 0.5 Fe 0.5 PO4 batteries at different scan rates, according to Figure 5 a, the CV curve of LiMn 0.5 Fe 0.5 PO4-PA battery at a scan rate of 0.1 mV / s, the Fe redox peak pressure difference was 0.09 V, and the Mn redox peak difference was 0.16 V; according to Figure 5 b, the CV curve of LiMn 0.5 Fe 0.5 PO4 battery at a scan rate of 0.1 mV / s, the Fe redox peak pressure difference was 0.14 V, and the Mn redox peak difference was 0.21 V. This proves that the battery assembled using the positive electrode material synthesized by FP-PA has better reversibility and impedance compared to the battery synthesized by the traditional method, which makes such a battery show better rate performance. In addition, Figure 6 The in-situ impedance diagrams of the two batteries of (a) (b) also show the same results.

[0045] Figure 7 and Figure 8 the rate performance and cycle stability diagrams of the batteries assembled from the two materials. Figure 7 show that under different rates (1C = 170 mAh / g), 2.5 V-4.5 V voltage, LiMn 0.5 Fe 0.5The discharge specific capacity of PO4-PA battery at 0.1C, 0.2C, 0.5C, 1C, 2C and 5C is 154.6 mAh / g, 149 mAh / g, 139.6 mAh / g, 130.7 mAh / g, 119.5 mAh / g and 103 mAh / g, respectively, while that of LiMn 0.5 Fe 0.5 The discharge specific capacity of PO4 battery at 0.1C, 0.2C, 0.5C, 1C, 2C and 5C is 137.8 mAh / g, 126.7 mAh / g, 111 mAh / g, 99.2 mAh / g, 87.2 mAh / g and 72 mAh / g, respectively. The positive electrode material synthesized by the method has better rate performance and discharge specific capacity. Figure 8 The LiMn 0.5 Fe 0.5 The capacity retention of PO4-PA battery after 350 cycles at 1C rate is 91.4%, while that of LiMn 0.5 Fe 0.5 The capacity retention of PO4 battery after 350 cycles at 1C rate is 79.3%, while that of LiMn 0.5 Fe 0.5 PO4-PA battery shows better cycle stability.

Claims

1. The present invention provides a method for obtaining high-performance precursors from waste lithium iron phosphate to prepare lithium manganese iron phosphate, characterized by, The method comprises the following steps: (1) Discharge and disassemble the waste lithium iron phosphate battery in salt water to obtain lithium iron phosphate positive electrode sheet, graphite negative electrode sheet and diaphragm. (2) Treat the obtained lithium iron phosphate positive electrode sheet in a muffle furnace at 500`C to obtain waste lithium iron phosphate positive electrode powder and aluminum foil. (3) Weigh a certain amount of waste lithium iron phosphate positive electrode powder and disperse it in a certain amount of sulfuric acid solution, and place it in an 80`C oil bath to dissolve it. (4) Add a certain amount of phytic acid solution and iron sulfate so that the molar number of phosphorus and iron elements is the same. (5) Add a certain amount of alkaline solution to adjust the pH of the above solution to about 2 to obtain hydrated iron phosphate; add sodium carbonate and wash the precipitate with deionized water to obtain lithium carbonate. (6) In a tube furnace, inert gas is introduced and calcined at high temperature for a certain time to obtain dehydrated iron phosphate (FP-PA).

2. The present application as claimed in claim 1, wherein a method for obtaining high performance precursor from waste lithium iron phosphate to prepare lithium manganese iron phosphate is disclosed. In step (3), the ratio of waste lithium iron phosphate powder to deionized water is 2-5g / 100ml.

3. The present application as claimed in claim 1, wherein a method for obtaining high performance precursor for preparing lithium manganese iron phosphate from waste lithium iron phosphate is disclosed. In step (4), the phosphorus content of added phytic acid is 3%-10% of the phosphorus content of waste lithium iron phosphate.

4. The present application as claimed in claim 1, wherein a method for obtaining high performance precursor for preparing lithium manganese iron phosphate from waste lithium iron phosphate is disclosed, wherein, In step (5), the alkaline solution is one of ammonia solution, sodium hydroxide solution and potassium hydroxide solution.

5. Iron dehydrated phosphate obtained by the preparation process according to claims 1-4, characterized by, Using phytic acid as a chelating agent, the fusion of iron phosphate particles is limited by high-temperature carbonization, and using it as a precursor for lithium manganese iron phosphate synthesis can effectively control the particle size of the material, thereby achieving high-quality recovery of waste lithium iron phosphate and improving the cycle stability and rate performance of lithium manganese iron phosphate materials.